1986
DOI: 10.1136/thx.41.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma in a hairdressing salon.

Abstract: Occupational asthma among hairdressers has been recognised for some years and cases of work related asthma due to hair bleaches containing persulphates and hair dyes have been reported. The extent of the disease among hairdressers remains unknown. An investigation was carried out on an entire hairdressing salon, which specialised in hair bleaching and colouring and which employed 23 staff. On the basis of history and specific and non-specific bronchial provocation testing, four out of 23 staff were found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 17 publications
3
83
0
3
Order By: Relevance
“…The results of the present study support the other cross-sectional studies that have found increased prevalence of respiratory symptoms in hairdressers, even after adjusting for smoking. [22][23][24][25] Even asymptomatic workers show prevalence of bronchial obstruction of 4.7%, which denotes the work exposure related upper airway obstruction. Symptomatic workers also show 28% bronchial obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study support the other cross-sectional studies that have found increased prevalence of respiratory symptoms in hairdressers, even after adjusting for smoking. [22][23][24][25] Even asymptomatic workers show prevalence of bronchial obstruction of 4.7%, which denotes the work exposure related upper airway obstruction. Symptomatic workers also show 28% bronchial obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…are capable of causing skin irritation, respiratory problems including bronchial irritation and occupational asthma, and other adverse symptoms through inhalation and dermal absorption. (23,27,28,29) Epidemiological evidence also suggests an elevated risk of cancer at several sites (particularly bladder and lung) for hairdressers with exposure to hair-care products. (27,30,31) Contact dermatitis is a well-recognized, and possibly the most frequent, occupational disease among cosmetologists.…”
Section: A Exposures To Chemical Agentsmentioning
confidence: 99%
“…Products that contain chemical allergens that have been associated with hypersensitivity in hairdressers include persulphate salts, dyes containing paraphenylenediamine, and permanent wave solutions. (23,24) VI. RESULTS…”
Section: Allergic Bronchoconstriction or Type I Hypersensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…19 This job-related exposure has been associated with a number of health concerns, primarily skin disorders, 9 -12 respiratory conditions, [12][13][14][15][16] and cancer. [17][18][19] Although correlation between hairdressing chemicals and neuropsychiatric symptoms has not been documented in the medical literature thus far, it is recognized that neurotoxicants can express themselves in a "plethora of possible endpoints," including neurobehavioral manifestations.…”
Section: Occupational Chemical Exposure Of Hairdressersmentioning
confidence: 99%